Dowtys aspect hypothesis segmented - Fernando, Tim (Proceedings of the Amsterdam Colloquium, 2013)
A form of the aspect calculus hypothesized in Dowty 1979 to explain the different aspectual properties of the various kinds of verbs is reinterpreted by chaining segments incrementally, as in Landman 2008. Segmenting an interval brings out, it is argued, a notion of event that can be represented at bounded but variable granularities by strings of sets of temporal propositions, tracking change. Simple accounts of telicity, durativity and composition interpreting Moens and Steedman 1988 are given in terms of such strings.